An??lise cinem??tica comparativa e discriminat??ria dos fatores proximais, locais e distais durante as subfases do apoio na descida de escadas entre mulheres com dor femoropatelar e assintom??ticas - Novello, Aline de Almeida (2016)
Evidences found in the literature are inconsistent and there is no consensus about the kinematic differences performed by women with patellofemoral pain (PFP) during stair descent, and there are no studies that have evaluated the tridimensional kinematics of the trunk, pelvis, hip, knee and ankle using a multisegmental model of the foot, simultaneously during this task in patients with PFP and evaluated separately the sub phases of stair descent. Therefore, the aim of this study was to compare the tridimensional kinematics of the trunk, pelvis and lower limbs in different sub phases of stair descent and identify the discriminatory capability of the kinematic variables among PFP and healthy women during this task. In this cross-sectional study, thirty-four women with PFP (PFP group) and thirty-four painless women (control group) between 18 and 35 years-old underwent kinematic evaluation during the stair descent. It was observed that kinematic differences between groups occurred only in the first double support phase of the stair descent and the variables of internal rotation of the hindfoot in relation to the tibia in the initial contact, the contralateral pelvic drop in the load-response, external rotation range of motion of the hindfoot in relation to the tibia and dorsiflexion of the forefoot in relation to the hindfoot were the variables that presented the best capacity to discriminate women with and without PFP. Therefore, our results provided a better understanding of the trunk, pelvis and lower limbs kinematics in different subphases of the support phase of stair descent in women with PFP.